Determinant Factors of Chronic Energy Deficiency (CED) in Pregnant Women: A Mixed-Methods Study - Sari, Marlynda Happy Nurmalita; Anggraini, Dina Dewi; Rahmawati, Ira; Widiani, Esti (Poltekkes Kemenkes Surakarta, 2025)
Background: This study investigates Chronic Energy Deficiency (CED) in expecting mothers, a condition arising from prolonged inadequate energy and protein intake. Untreated CED poses health risks for both mothers and their unborn babies, including miscarriage, premature birth, birth defects, low birth weight (LBW), and potentially stunting the child's growth. Despite existing goals, the incidence of CED in pregnant women remains above the target of 17.3%. Women with a mid-upper arm circumference (MUAC) less than 23.5 cm are considered at high risk. This research aims to identify factors contributing to the prevalence of CED among pregnant women in the Central Java and East Java regions. Methods: This study employs a mixed-methods approach, specifically a sequential explanatory design. A sample sized group of 124 participants was selected using simple random sampling. Questionnaires were distributed to healthcare facilities. In-depth interviews were subsequently conducted to delve deeper into the causes of CED and existing efforts to address it within the chosen health centers. Results: The final multivariate analysis revealed a significant association (p-value < 0.05) between CED in pregnant women and the following factors: income (p-value=0.018, OR=3), knowledge about CED (p-value=0.028, OR=2.7), dietary habit (p-value=0.015, OR=3.4), and food intake (p-value=0.007, OR=4). Conclusion: Food intake is a more dominant variable in relation to CED in pregnant women. Health workers are encouraged to continue enhancing health promotion efforts regarding nutritional intake for pregnant women and their families. In addition, community health centers should consistently support the provision of supplementary feeding programs for pregnant women through regular monitoring.